A silanol-functionalized polyoxometalate with excellent electron transfer mediating behavior to ZnO and TiO2 cathode interlayers for highly efficient and extremely stable polymer solar cells. Issue 6 (24th January 2018) - Tountas, Marinos; Topal, Yasemin; Verykios, Apostolis; Soultati, Anastasia; Kaltzoglou, Andreas; Papadopoulos, Theodoros A.; Auras, Florian; Seintis, Kostas; Fakis, Mihalis; Palilis, Leonidas C.; Tsikritzis, Dimitris; Kennou, Stella; et al.
Abstract : A silanol-functionalized polyoxometalate improves the electron collecting interface. Abstract : Combining high efficiency and long lifetime under ambient conditions still poses a major challenge towards commercialization of polymer solar cells. Here we report a facile strategy that can simultaneously enhance the efficiency and temporal stability of inverted photovoltaic architectures. Inclusion of a silanol-functionalized organic–inorganic hybrid polyoxometalate derived from a PW9 O34 lacunary phosphotungstate anion, namely ( n Bu4 N)3 [PW9 O34 ( t BuSiOH)3 ], significantly increases the effectiveness of the electron collecting interface, which consists of a metal oxide such as titanium dioxide or zinc oxide, and leads to a high efficiency of 6.51% for single-junction structures based on poly(3-hexylthiophene):indene-C60 bisadduct (P3HT:IC60 BA) blends. The above favourable outcome stems from a large decrease in the work function, an effective surface passivation and a decrease in the surface energy of metal oxides which synergistically result in the outstanding electron transfer mediating capability of the functionalized polyoxometalate. In addition, the insertion of a silanol-functionalized polyoxometalate layer significantly enhances the ambient stability of unencapsulated devices which retain nearly 90% of their original efficiencies ( T 90 ) after 1000 hours.